The Implementation Of Patient And Family Education, And Effective Communication In A Hospital At South Sulawesi: An Action Research Study - Liza Fauzia; Syahrul Syahrul; Saldy Yusuf; Abdul Majid (Poltekkes Kemenkes Surakarta, 2021)
Background: Frequent phenomena found in hospitals are lack of health education, unclearness medical information delivery, poor communication, or even nurses tried to neglect the importance of health information to patients. To identify problems related to the implementation of effective education and communication in one of hospitals in South Sulawesi Province. Methods: The study used qualitative and quantitative. This action research study involved 30 nurses consisting primary nurses and manager nurses in surgical care room, intesive care room, child care room and internal care room. Problem identification and the implementation is conducted. Analysis of data from the results of the distribution of questionnaires with descriptive statistics, while the results of interviews with content analysis. The questionnaires and interview guidelines were based on the 2012 Hospital Accreditation Rules. Results: Based on interviews and questionnaire distribution, Main problems identified in this study were less education and effective communication for patiens and patiens’ family. Moreover, socialization and provision of standard operational procedure (SOP) for education for patiens and patiens’ family was not available yet. Based on the the problem identification, in-house training for implementation of patiens and patiens’ family education and effective communication were conducted for the nurses. SOP about giving information and education for patient or patient’s family were made. Conclusion: It was proven that patiens and patiens’ family education and effective communication contributed to improve the quality of health services.